Minor Stroke and Transient Ischemic Attack: Research and Practice - Yakhkind, Aleksandra (Front Neurol, 2016)
A majority of patients with ischemic stroke present with mild deficits for which aggressive management is not often pursued. Comprehensive work-up and appropriate intervention for minor strokes and transient ischemic attacks (TIAs) point toward better patient outcomes, lower costs, and fewer cases of disability. Imaging is a key modality to guide treatment and predict stroke recurrence. Patients with large vessel occlusions have been found to suffer worse outcomes and could benefit from intervention. Whether intravenous thrombolytic therapy decreases disability in minor stroke patients and whether acute endovascular intervention improves functional outcomes in patients with minor stroke and known large vessel occlusion remain controversial. Studies are ongoing to determine ideal antiplatelet therapy for stroke and TIA, while ongoing statin therapy, surgical management for patients with carotid stenosis, and anticoagulation for patients with atrial fibrillation have all been proven to decrease the rate of stroke recurrence and improve outcomes. This review summarizes the current evidence and discusses the standard of care for patients with minor stroke and TIA.